2019
DOI: 10.1002/ptr.6487
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resveratrol Supplementation on Cardio‐Metabolic Risk Factors in Patients with Type 2 Diabetes: A Randomized, Double‐Blind Controlled Trial

Abstract: The aim of the present randomized controlled trial was to evaluate the effect of a micronized resveratrol supplement on glycemic status, lipid profile, and body composition in patients with type 2 diabetes mellitus (T2DM). A total of 71 overweight patients with T2DM (body mass index ranged 25–30) were randomly assigned to receive 1000 mg/day trans‐resveratrol or placebo (methyl cellulose) for 8 weeks. Anthropometric indices and biochemical indices including lipid and glycemic profile were measured before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 69 publications
(83 reference statements)
1
36
0
Order By: Relevance
“…A second meta-analysis of clinical studies with resveratrol in T2D patients (nine randomized controlled trials with 283 subjects) reported that resveratrol could significantly reduce levels of FBS with concomitant beneficial effects on HOMA-IR scores and levels of insulin [42]. Very recently, a randomized clinical trial involving 71 overweight patients with T2D reported that eight-week resveratrol supplementation was able to significantly improve cardiac and metabolic parameters [46]. Furthermore, another recent randomized, double-blind, placebo-controlled trial with 56 patients having T2D and coronary artery disease reported that resveratrol reduced hyperglycemia and levels of MDA and improved the levels of HDL-cholesterol, the total-/HDL-cholesterol ratio, and TAC [47].…”
Section: Discussionmentioning
confidence: 99%
“…A second meta-analysis of clinical studies with resveratrol in T2D patients (nine randomized controlled trials with 283 subjects) reported that resveratrol could significantly reduce levels of FBS with concomitant beneficial effects on HOMA-IR scores and levels of insulin [42]. Very recently, a randomized clinical trial involving 71 overweight patients with T2D reported that eight-week resveratrol supplementation was able to significantly improve cardiac and metabolic parameters [46]. Furthermore, another recent randomized, double-blind, placebo-controlled trial with 56 patients having T2D and coronary artery disease reported that resveratrol reduced hyperglycemia and levels of MDA and improved the levels of HDL-cholesterol, the total-/HDL-cholesterol ratio, and TAC [47].…”
Section: Discussionmentioning
confidence: 99%
“…It also resulted in a decrease in the level of MDA and an increase in TAC in patients with T1D [ 39 ]. In patients with T2D, almost the same effect was happened [ 40 , 41 ]. However, an invalid prescription has been reported in T2D patients, which is due to the complexity of human genetics and other factors [ 42 ].…”
Section: Non-flavonoidsmentioning
confidence: 79%
“…Both RSV supplementation and ER did not change serum hs-CRP, glucose, and HOMA-IR significantly at the end of the study. There is evidence that 1000 mg/day of RSV may reduce glycemia [ 44 ]. However, it seems that beneficial effects of RSV on glucose metabolism occur when administration dose is higher than 500 mg and in a period higher than 10 weeks, explaining why in the present 30-day intervention study there were no significant alterations observed [ 45 ].…”
Section: Discussionmentioning
confidence: 99%